The effects of repressive actions to movement solidarity of the members of Bayan Muna and Kilusang Mayo Uno (KMU). - Gallos, Nuelene N.
The members of social movement organizations (SMOs) have been the subject of repressive actions because of challenging status quo. Despite experiencing repressive actions, there are still members who identify their common interests with the other members and turn the potential into collective action. Interviewing the leaders and surveying the members of the two organizations with additional archival materials from Commission of Human Rights, U.S. Department of State and KARAPATAN, this study examines the effects of repressive actions to movement solidarity of members of Bayn Muna Kilusang Mayo Uno (KMU). The study has found out that there is minimal existence of repressive actions and movement solidarity in the five sample organizations, thus the existence of the two variables is far from conclusive.